Demonstrasi Pemberian Suara Ibu Sebagai Upaya Peningkatan Pengetahuan Perawat Terhadap Perubahan Heart Rate Bayi Prematur - Noerma Shovie Rizqiea; Ratih Dwilestari Puji Utami; Tresia Umarianti; Rufaida Nur Fitriana (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: Premature birth occurs before 37 weeks of complete gestation, weighs less than 2,500 grams, and is the main cause of newborn death and the second cause of death in children under five. Premature babies are at higher risk for illness, disability, and death. Changes in heart rate in premature babies can occur after being given a recording of the mother's voice, which contains 3 types: speaking, reading, and singing. The results showed an effect of recording the mother's voice on changes in heart rate in premature infants. This community service activity aims to increase nurses' knowledge about the importance of the mother's voice on changes in the heart rate of premature babies. Methods: Community service activities were carried out twice. The first activity was carried out through a zoom meeting which explained the importance of the mother's voice in premature babies with the help of PowerPoint media. Then continued, the second activity in the form of a demonstration of Mother's voting. Results: The pre-test showed that 9 nurses (100%) had less knowledge about the importance of the mother's voice for the heart rate of premature babies. After receiving education and demonstration regarding the mother's voting, the post-test results were that 7 nurses (78%) had good knowledge and 2 nurses (22%) had poor knowledge. Conclusion: Nurses become aware of the importance of the mother's voice in increasing the heart rate of premature babies.